THE PURPOSE AND SIGNIFICANCE OF TEACHING CIVIL DEFENSE IN MODERN CONDITIONS (International journal of medical sciences, 2025)
This article examines the system of civil defense in the Republic of Uzbekistan, its main tasks, and the organizational structure at the national and local levels. It highlights the role of civil defense in protecting the population, economic facilities, and cultural values during military operations and emergencies. The functions of emergency management bodies, the establishment of the Ministry of Emergency Situations, and the responsibilities of local authorities are discussed. The paper also emphasizes the importance of readiness, coordination, and proper training of civil defense personnel in preventing and mitigating emergency situations.